Noise level spread in the vicinity of a crossroads - Walerian, E.; Janczur, R.; Czechowicz, M. (Archives of Acoustics, 2005)
In the paper, the PROP10 program is used to present the time-average sound level on façades of buildings in the vicinity of a crossroads. The propagation model within an urban system forming canyon streets includes the wave interaction with obstacles, multi-reflections from building walls and single and double diffraction at their wedges. For the current purpose the program is provided with a road model in which the vehicle route is divided into sub-segments with lengths and linear densities of emitted energy that depend on the traffic organization in the vicinity of the crossroads. The lengths of the sub-segments, where vehicles wait and are forced to a subsequent start and stop, depend on the flow rates on lanes, the equivalent vehicle length, the red and green light times and the speed of leaving a crossroads. The linear energy density at these sub-segments depends on a parameter characterizing the energy emitted during the starting of a vehicle. The time-average sound level is analyzed as a function of the enumerated parameters. Key words: traffic noise, interrupted movement, canyon street.